Benjamin, the method of comprehension and dialetical images - Pinto Coelho, Cláudio Novaes; Persichetti, Simonetta (Folios, revista de la Facultad de Comunicaciones y Filología, 2018)
In this paper we aim to reflect on Walter Benjamin's view regarding dialetical images. The reflection will be based on a comparison between authors who are linked to the comprehensive method, e.g. Weber and Heidegger, and authors who were bound to the Frankfurt. School, such as Adorno, Horkheimer and Walter Benjamin himself. We argue that the benjaminian view on dialectics has specific features that are derivative from his investigations on the bonds between images, consumption objects and urban spaces.